Halogen Bonds in 2,5-Dihalopyridine-Copper(I) Halide Coordination Polymers - von Essen, Carolina (Materials (Basel), 2019)
Two series of 2,5-dihalopyridine-Cu(I)A (A = I, Br) complexes based on 2-X-5-iodopyridine and 2-X-5-bromopyridine (X = F, Cl, Br and I) are characterized by using single-crystal X-ray diffraction analysis to examine the nature of C2−X2···A–Cu and C5−X5···A–Cu halogen bonds. The reaction of the 2,5-dihalopyridines and Cu(I) salts allows the synthesis of eight 1-D coordination polymers and a discrete structure. The resulting Cu(I)-complexes are linked by C−X···A–Cu halogen bonds forming 3-D supramolecular networks. The C−X···A–Cu halogen bonds formed between halopyridine ligands and copper(I)-bound halide ions are stronger than C−X···X’–C interactions between two 2,5-dihalopyridine ligands. The C5−I5···I–Cu and C5−Br5···Br–Cu halogens bonds are shorter for C2-fluorine than C2-chlorine due to the greater electron-withdrawing power of fluorine. In 2,5-diiodopyridine-Cu(I)Br complex, the shorter C2−I2···Br–Cu [3.473(5) Å] distances are due to the combined polarization of C2-iodine by C2−I2···Cu interactions and para-electronic effects offered by the C5-iodine, whilst the long halogen bond contacts for C5−I5···Br–Cu [3.537(5) Å] are indicative that C2-iodine has a less para-electronic influence on the C5-iodine. In 2-fluoro-5-X-pyridine-Cu(I) complexes, the C2-fluorine is halogen bond passive, while the other C2-halogens in 2,5-dihalopyridine-Cu(I), including C2-chlorine, participate in halogen bonding interactions.